2019
DOI: 10.3390/cells8060540
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor Signaling in Skin Cancers

Abstract: Fibroblast growth factor (FGF)/Fibroblast growth factor receptor (FGFR) signaling regulates various cellular processes during the embryonic development and in the adult organism. In the skin, fibroblasts and keratinocytes control proliferation and survival of melanocytes in a paracrine manner via several signaling molecules, including FGFs. FGF/FGFR signaling contributes to the skin surface expansion in childhood or during wound healing, and skin protection from UV light damage. Aberrant FGF/FGFR signaling has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 158 publications
1
54
0
Order By: Relevance
“…Analysis of whole-exome sequencing data revealed only a few mutations previously identified as associated with acquired resistance to targeted drugs. It is in line with the current view that in parallel to genetic alterations, melanoma cell-autonomous mechanisms of resistance can rely on complex transcriptomic adaptations supported by epigenetic regulations, including miRNA-mediated mechanisms, and extended by the interplay between tumor and stromal cells that involves cell-cell interactions, paracrine stimulation and extracellular vesicles to create a resistance-permissive niche [39][40][41][42][43][44][45][46]. Mechanisms of resistance primarily directed to support proliferation and survival of cancer cells implicate a plethora of transcriptional regulators, adaptive responses, and feedback loops that extensively affect melanoma cell phenotype enabling the expansion of distinct cell subpopulations in the presence of drug(s) [27,[47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 84%
“…Analysis of whole-exome sequencing data revealed only a few mutations previously identified as associated with acquired resistance to targeted drugs. It is in line with the current view that in parallel to genetic alterations, melanoma cell-autonomous mechanisms of resistance can rely on complex transcriptomic adaptations supported by epigenetic regulations, including miRNA-mediated mechanisms, and extended by the interplay between tumor and stromal cells that involves cell-cell interactions, paracrine stimulation and extracellular vesicles to create a resistance-permissive niche [39][40][41][42][43][44][45][46]. Mechanisms of resistance primarily directed to support proliferation and survival of cancer cells implicate a plethora of transcriptional regulators, adaptive responses, and feedback loops that extensively affect melanoma cell phenotype enabling the expansion of distinct cell subpopulations in the presence of drug(s) [27,[47][48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 84%
“…In this context, the fibroblast growth factor/fibroblast growth factor receptor (FGF/FGFR) system has recently attracted increasing interest due to its role in tumor growth, metastasis, and resistance to anti-cancer therapies [ 7 , 8 ]. For instance, aberrant FGF/FGFR activation may occur in both a ligand-dependent and ligand-independent manner in several tumors, including breast cancer [ 8 , 9 , 10 , 11 , 12 , 13 ]. Experimental and clinical evidence has also shown that deregulated FGF/FGFR signaling may elicit an oncogenic action [ 14 , 15 , 16 , 17 ], though some reports have indicated that the FGF/FGFR axis may exert an anticancer action in certain contexts [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…FGFRs are a subfamily of tyrosine kinase receptors; the family has four members (FGFR‐1–4) in mice, and these proteins are expressed in a wide variety of cell types (Eswarakumar et al, 2005; Czyz, 2019; Dai et al, 2019). To measure the expression levels of FGFR‐1–4 in ASCs, we examined FGFR messenger RNA (mRNA) expression in the presence of different concentrations of FGF‐2.…”
Section: Resultsmentioning
confidence: 99%
“…FGF‐2 binds to FGFR‐1–4 to mediate downstream signaling through pathways such as mitogen‐activated protein kinase (MAPK) signaling (Eswarakumar et al, 2005; Czyz, 2019), thereby regulating cellular proliferation, differentiation, and migration. To examine the downstream effectors of FGFR signaling in the regulation of ASCs, the phosphorylation of ERK1/2, p38α, and JNK1/2/3 was examined after the addition of 5 ng/mL FGF‐2 into the medium.…”
Section: Resultsmentioning
confidence: 99%